2009
DOI: 10.1111/j.1399-0004.2009.01193.x
|View full text |Cite
|
Sign up to set email alerts
|

Valuing the benefit of diagnostic testing for genetic causes of idiopathic developmental disability: willingness to pay from families of affected children

Abstract: Idiopathic developmental disability (DD) has been found to put significant psychological distress on families of children with DD. The cause of the disability, however, is unknown for up to one-half of the affected children. Chromosomal abnormalities identified by cytogenetic analysis are the most frequently recognized cause of DD, although they account for less than 10% of cases. Array genomic hybridization (AGH) is a new diagnostic tool that provides a much higher detection rate for chromosomal imbalance tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 33 publications
3
59
0
Order By: Relevance
“…As a preliminary step in exploring personal utility, at least one project will conduct a discrete-choice experiment that can provide estimates of the value patients place on different types of incidental findings. 60 …”
Section: Conceptual Domainsmentioning
confidence: 99%
“…As a preliminary step in exploring personal utility, at least one project will conduct a discrete-choice experiment that can provide estimates of the value patients place on different types of incidental findings. 60 …”
Section: Conceptual Domainsmentioning
confidence: 99%
“…To elicit preferences between alternatives and to esti mate personal utility and willingness to pay, we used a discretechoice experiment. [11][12][13][14][15][16] In genomic medicine, personal utility is the worth that an individual ascribes to a genomic test. 17 In economics, personal utility is quantified as a measure of wellbeing determined by eliciting individuals' choices between different goods.…”
Section: Methodsmentioning
confidence: 99%
“…We included cost as a continuous vari able. 14 We specified that attributes representing the threshold level for lifetime risk of disease, the treatability and severity of incidentally iden tified diseases, and information on carrier status would follow normal distributions. This allowed participants to have heterogeneous values for these attributes relative to the reference level.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…WTP methods have recently been applied to different types of genetic tests in general (Ries et al 2010) and to genetic tests for unexplained developmental disability (Regier et al 2009). In WTP surveys, individuals trade off the utility they expect to gain from the test in question with the utility from alternative uses of their money.…”
Section: Balancing the Benefits And Harms Of Genetic Testsmentioning
confidence: 99%
“…A recent Canadian study found that few people were willing to pay the full cost of a molecular genetic test, in part because they felt that this was the responsibility of health payers (Ries et al 2010). WTP can also be estimated through choice experiment (conjoint analysis) surveys in which individuals are asked to trade off among bundles of attributes, including cost and the probability of detection (Regier et al 2009). Due to a number of methodological limitations (Donaldson et al 2006), the use of WTP techniques has to be handled with care.…”
Section: Balancing the Benefits And Harms Of Genetic Testsmentioning
confidence: 99%